BUDIDAYA JAMUR PERUSAK KAYU II. PENILAIAN EFISIENSI BIOLOGI PADA MEDIA DARI LIMA BELAS JENIS KAYU - Sihati Suprapti (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Oyster mushroom was cultivated on sawdust media of damar (Agathis sp), durian (Durio zibethinus Murr.), teak. (Tectona grandis L.f), jeungjing (Albizia falcataria (L.) Fosb.), rubber (Hevea brasiliensis Muell. Arg.), coconut (Cocos nucifera L.), kemang (Mangifera caesia Jack), manii (Maesopsis eminii Engl.), meranti merah (Shorea johorensis Foxw.), nangka (Artocarpus integra Merr.), pulai (Alstonia scholaris R.Br.), sehiye (Sterculia macrophylla Vent.), shiega (Celtis latifolia Planch.), sihara (Ganophyllum falcatum BL.) and pine (Pinus merkusii Jung et De Vr.). The composition of the media was 77,5 % sawdust mixed with 20 % rice bran, 0,5 % lime, 0,5 % trisuperhosphate and 1,5 % gypsum. Each media was mixed with distilled water 125 - 150 % per dry weight of media. The media was cooled after autoclave sterilization before being inoculated with pure culture of the mushroom. The mature mushroom was harvested daily after the growth of the fruiting body. Biological Efficiency (BE) was calculated based on the yield of fresh mushroom in proportion with the dry weight of material used as media.The higher BE was obtained from rubber wood sawdust media (86.15 %), nangka (66.26 %), kemang (63,85%) and pulai (63.52). The lowest BE was obtained from damar (28.22 %).